2011
DOI: 10.5194/acp-11-8945-2011
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of size and time resolved trace elements and organic aerosols from an urban courtyard site in Switzerland

Abstract: Abstract. Time and size resolved data of trace elements were obtained from measurements with a rotating drum impactor (RDI) and subsequent X-ray fluorescence spectrometry. Trace elements can act as indicators for the identification of sources of particulate matter <10 μm (PM10) in ambient air. Receptor modeling was performed with positive matrix factorization (PMF) for trace element data from an urban background site in Zürich, Switzerland. Eight different sources were identified for the three examined size… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(71 citation statements)
references
References 57 publications
6
64
1
Order By: Relevance
“…Bourcier et al (2012) studied PM 1 concentrations and seasonal variability over one year at the high altitude site of puy de Dôme in France. However, of the studies mentioned, source apportionment was only performed for PM 1 at urban sites by Vecchi et al (2008) and Richard et al (2011). Minguillón et al (2012) performed source apportionment of PM 1 at a rural site in Switzerland but only for short measurement campaigns during summer and winter.…”
Section: Cusack Et Al: Source Apportionment Of Pm 1 and Sub-micromentioning
confidence: 99%
See 2 more Smart Citations
“…Bourcier et al (2012) studied PM 1 concentrations and seasonal variability over one year at the high altitude site of puy de Dôme in France. However, of the studies mentioned, source apportionment was only performed for PM 1 at urban sites by Vecchi et al (2008) and Richard et al (2011). Minguillón et al (2012) performed source apportionment of PM 1 at a rural site in Switzerland but only for short measurement campaigns during summer and winter.…”
Section: Cusack Et Al: Source Apportionment Of Pm 1 and Sub-micromentioning
confidence: 99%
“…Thus, understanding the chemical composition and sources of fine PM and sub-micron particles is vital. Of the few studies performed on PM 1 , most are concerned with the urban environment, and were characterised during short measurement campaigns (Vecchi et al, 2008;Richard et al, 2011). Cozic et al (2008) published results on organic and inorganic compounds in PM 1 for 7 years at a high alpine site in Switzerland (Jungfraujoch).…”
Section: Cusack Et Al: Source Apportionment Of Pm 1 and Sub-micromentioning
confidence: 99%
See 1 more Smart Citation
“…Using one-or two-hour resolution metal data in receptor modeling analyses has proven to be useful in the identification of local aerosol sources in urban areas 30 (Richard et al, 2011;Dall'Osto et al, 2013). These previous studies found local urban dust factors such as road dust, brake dust, and local industrial sources, which typically occur sporadically and last only a few hours at most.…”
mentioning
confidence: 99%
“…Particles in the accumulation mode (0.1-1 µm) can be used as tracers of pyrotechnic activity (Wehner et al, 2000; Nicolás et al, 2009;Richard et al, 2011;Crespo et al, 2014). In the present work, we have selected the particle number concentration (PNC) in the 0.25-0.28 µm size channel as an indirect indicator of the arrival of the plume to the sampling site.…”
Section: O 3 and Particlesmentioning
confidence: 99%